The Microbiome in Primary Sclerosing Cholangitis: Current Evidence and Potential Concepts - Hov, Johannes R.; Karlsen, Tom H. (Seminars in Liver Disease, 2017)
The close relationship between primary sclerosing cholangitis (PSC) and inflammatory bowel disease has inspired hypothetical models in which gut bacteria or bacterial products are key players in PSC pathogenesis. Several studies using high-throughput sequencing technology to characterize the gut microbiota in PSC have been published over the past years. They all report reduced diversity and significant shifts in the overall composition of the gut microbiota. However, it remains unclear as to whether the observed changes are primary or secondary to PSC development and further studies are needed to assess the biological implications of the findings. In the present article, we review the published data in perspective of similar studies in other diseases. We discuss aspects of methodology and study design that are relevant to interpretation of the data. Furthermore, we propose that interpretation and further assessments of findings are structured into conceptual compartments, and elaborate three such possible concepts relating to immune function (the “immunobiome”), host metabolism (the “endobiome”), and dietary and xenobiotic factors (the “xenobiome”) in PSC.
Keywords: primary sclerosing cholangitis; microbiota; dysbiosis; liver disease